Endoscopic laser resection of a ureteral tumour in primary multiple malignant neoplasms - B. G. Guliev; B. K. Komyakov; Zh. P. Avazkhanov (Вестник урологии, 2021)
A case of the ureteral tumour endoscopic treatment is presented in a patient with primary multiple malignancies. In the case of polyneoplasia, there are usually two or more neoplasms of different localizations, including the organs of the urinary system. The kidney and prostate tumours are diagnosed more often, but in rare cases, ureter neoplasms. It is especially important to perform organ-sparing surgeries when diagnosing ureter neoplasms. In addition, chronic kidney disease after radical nephroureterectomy can be a relative contraindication to further chemoradiation therapy in polyneoplasias. In this patient, along with the breast and vulva neoplasms, a solitary tumour of the right ureter's lower third was detected, which was successfully removed endoscopically. The chosen method of minimally invasive treatment allowed to preserve a normal functioning kidney, to avoid the development of chronic kidney disease in the patient, who was later scheduled for chemotherapy.